Inside the red box : North Korea's post-totalitarian politics - McEachern, Patrick 1980- (Contemporary Asia in the world, 2010)
Post-totalitarian institutionalism -- Historical context -- North Korea's political institutions -- Institutional jostling for agenda control, 1998-2001 -- Segmenting policy and issue linkages, 2001-2006 -- Policy reversals, 2006-2008